THE SYSTEM OF INFORMATION MANAGEMENT AS THE KEY COMPONENT FOR EFFECTIVENESS INCREASE OF THE STATE REGULATION OF INSTITUTIONAL CHANGES (INNOVATIVE ECONOMY, 2020)
Zhelizko O.O. THE SYSTEM OF INFORMATION MANAGEMENT AS THE KEY COMPONENT FOR EFFECTIVENESS INCREASE OF THE STATE REGULATION OF INSTITUTIONAL CHANGESPurpose. The aim of the article is to develop and implement the system of information management within the effectiveness increase of the state regulation of institutional changes in the context of management of economic security of entrepreneurship and the national system of economic security of entrepreneurship in Ukraine.Methodology of research. Within the research the following methods have been used: analysis and synthesis – to detect problems of information management of the state regulation of institutional changes in Ukraine; induction and deduction – to create and provide features of the system of information management of the state regulation of institutional changes in the country; graphical – to provide the appropriate information.Findings. The scientific article has identified the low level of performance of the state regulation of institutional changes in Ukraine. It has also been stated that such a situation adversely affects economic security of entrepreneurship and functioning of the national system of economic security of entrepreneurship in the country. Separately, the relationship between cost-efficiency, quality, effectiveness and performance of the state regulation of institutional changes has been studied. To use an appropriate system of information management is suggested as one of the ways to increase performance of the state regulation of institutional changes in Ukraine. Within the formation and operation of the system developed and introduced, the data obtained in the paper have suggested using the appropriate mechanism.Originality. The research has further developed the detection of relationship between cost-efficiency, quality, effectiveness and performance of the state regulation of institutional changes, which unlike existed ones is aimed at provision of the appropriate level of economic security of entrepreneurship and the appropriate operation of SESE in the country. In addition, the research has improved the system of information management of the state regulation of institutional changes, which in contrast to the current ones is based on the appropriate mechanism of its formation.Practical value. The results of scientific research can be used to increase the performance of the state regulation of institutional changes in the context of economic security of entrepreneurship management as well as management of the national system of economic security of entrepreneurship in Ukraine.Key words: state regulation; economic security of entrepreneurship; cost-efficiency; effectiveness; institutional changes; information management; mechanism; performance; system; quality.
Keywords: Key words; state regulation; economic security of entrepreneurship; cost-efficiency; effectiveness; institutional changes; information management; mechanism; performance; system; quality.